2015
DOI: 10.1007/s12539-015-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

Deblurring Computed Tomography Medical Images Using a Novel Amended Landweber Algorithm

Abstract: In computed tomography (CT), blurring occurs due to different hardware or software errors and hides certain medical details that are present in an image. Image blur is difficult to avoid in many circumstances and can frequently ruin an image. For this, many methods have been developed to reduce the blurring artifact from CT images. The problems with these methods are the high implementation time, noise amplification and boundary artifacts. Hence, this article presents an amended version of the iterative Landwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Next, we removed AWGN using Shearlet [31]. For image deblurring, we finally selected the Amended Landweber (ALW) [59] algorithm.…”
Section: Our Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we removed AWGN using Shearlet [31]. For image deblurring, we finally selected the Amended Landweber (ALW) [59] algorithm.…”
Section: Our Proposalmentioning
confidence: 99%
“…Ref. [59] proposed a novel improved Landweber algorithm to eliminate blur from computed tomography (CT) medical images. The Landweber algorithm is a popular iterative algorithm for image deblurring, but it has the problems of slow convergence and noise sensitivity.…”
Section: Image Deblurring: Amended Landweber (Alw) Algorithmmentioning
confidence: 99%
“…The deblurring procedure uses the Richardson-Lucy (RL) algorithm initially developed to restore blurred images in optics [2,3]. Over time the algorithm found uses in other fields, such as astronomy [4] and medical image analysis [5], to list a few. Furthermore, in high-energy physics, an analogous procedure was developed [6], and more recently it has been demonstrated that the method can be utilized in nuclear physics [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Es muy común que estas imágenes no puedan ser tomadas de nuevo, lo que obliga a restaurarlas a su estado original para mejorar su nitidez antes de poder realizar otros pasos, como la detección, la segmentación, la clasificación [1]. En este sentido la restauración de imágenes juega un papel muy importante en áreas como: la tomografía computarizada [2], la tomografía de capacitancia y de impedancia eléctrica [3], el reconocimiento facial [4], la teledetección [5] y otras aplicaciones.…”
Section: Introductionunclassified